The State, the Writer, and the Politics of Memory - Elisabeth Mudimbe-Boyi (Studies in 20th & 21st Century Literature, 1999)
In L'Histoire sous surveillance (History Under Surveillance) Marc Ferro refers to what he calls the "silences of official history"…
Keywords: L' Histoire sous surveillance; History Under Surveillance; Marc Ferro; silences of official history